Etnososio : Pembelajaran Sosiologi Berbasis Kearifan - Abdurrohman, Abdurrohman; Suastra, I Wayan; Putu Arnyana, I Bagus; Herlina, Nurlaili (Universitas Hamzanwadi, 2024)
This research aims to examine the meanings embedded in the ritual of